1979
DOI: 10.1088/0022-3727/12/10/010
|View full text |Cite
|
Sign up to set email alerts
|

Flush probe studies of plasma flow over a flat plate: theory

Abstract: The transient electrical properties of a planar probe which is immersed in a flowing continuum plasma and in which the flow velocity is parallel to the probe surface are studied theoretically. When the probe is pulsed negatively, the resultant ion current overshoots its final equilibrium value. The time constant for recovery from this overshoot is shown to yield the information about the plasma flow over the probe. When the plasma sheath edge is inside the hydrodynamic boundary layer it is able to directly pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The first one is the 'one-sided probe' when one side of the planar probe is insulated. Such probes are used extensively for the diagnostics of the flowing plasma [13,14] and for the diagnostics of electron distribution function anisotropy [15]. The 2D simulation of such one-sided probes in the collisionless regime of ion motion was performed by Stamate [16,17] for a broad range of discharge regimes and types of ions.…”
Section: Introductionmentioning
confidence: 99%
“…The first one is the 'one-sided probe' when one side of the planar probe is insulated. Such probes are used extensively for the diagnostics of the flowing plasma [13,14] and for the diagnostics of electron distribution function anisotropy [15]. The 2D simulation of such one-sided probes in the collisionless regime of ion motion was performed by Stamate [16,17] for a broad range of discharge regimes and types of ions.…”
Section: Introductionmentioning
confidence: 99%
“…A signal-averaging digital oscilloscope was used for noise rejection and the ion current relaxation time was determined by data analysis on a PDP 11/10 minicomputer. Details of this analysis can be found elsewhere (Giles 1978).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous theoretical paper (Giles et al 1979) we have shown that the transient response of probe current to a negative step function yields information about the flow velocity in the vicinity of the probe. By varying the thickness of the DC ion sheath surrounding the probe it would in principle be possible to map the velocity profile through the hydrodynamic and thermal boundary layers.…”
Section: Introductionmentioning
confidence: 98%